Implementation and evaluation of a teacher intervention program on classroom communication - Karjalainen, Suvi; Sahlén, Birgitta; Falck, Andreas; Brännström, Jonas; Lyberg-Åhlander, Viveka (Logopedics, phoniatrics, vocology, 2020)
Background: Media frequently report on overall work-place challenges in Swedish schools, including teachers' working conditions, their well-being, and students' declining results. Language is the key to success in every school subject. Therefore, optimal language learning environments are important. Poor sound environments affect teachers' vocal health, their general well-being, and students' performance. To provide better conditions for teachers and students, it is necessary to combine optimized room acoustics with other preventive measures such as vocal training and evidence-based tools to improve classroom communication. Teachers play a key role in the classroom and need knowledge and skills in communicative strategies to ensure first-class communication. The purpose of this study is to explore the effects of an intervention program for primary-school teachers comprising strategies for enhanced language learning and interactions in the classroom, with focus on teachers' verbal and body communication (voice, gaze, and gesture). Methods: Teachers (n = 25) from seven schools teaching in school year 3-6 participated. Assessments were made pre/post intervention and at 5-weeks and 3-months follow-up. The assessments included teachers' self-assessments (questionnaires) of vocal health, self-efficacy, stress, burnout, and psychosocial work-environment. Results: The main results were significant decrease in voice problems at the 3-months follow-up and significant decrease of both stress and degree of burnout at 5-weeks follow-up. Self-efficacy score had increased significantly at 5-week follow-up. Conclusion: It can be concluded that the intervention program improves teachers' self-reported vocal health, decreases their perception of stress, and degree of burnout whilst increasing their sense of self-efficacy in classroom management.